BUILDING DEFENSE POWER THROUGH RENEWABLE ENERGY MANAGEMENT BASED ON LOCAL WISDOM - Khotimah, Khusnul (Jurnal Pertahanan dan Bela Negara, 2018)
Human Resources (HR) is one of the potential sources for building non-military defense forces for Indonesia. However, the condition of Indonesian human resources has many challenges amid the existing pluralistic conditions of society. One of them is by creating a community that is united in national pluralism. The research method used in this study is literature study and observation of previous research. The result is an analysis on the use of local wisdom in managing renewable energy towards energy independence to support national defense forces, through the application of the basic principles of community participation which include: (1) The community mobilizes and facilitates other communities to provide energy independently and contribute to the growth of people’s economy in support of national defense; (2) Management of renewable energy through community participation is expected to not only be a normative suggestion, but must be strengthened with regulations that regulate the active involvement of the community in supporting the achievement of 23% renewable energy mix program by 2025. Keywords: defense power, plural society, energy